Specificity and bioavailability of photosensitizers: In the search of an optimized photosensitizer for photodynamic therapy - Tsubone, Tayana Mazin (2017)
For several decades, Photodynamic Therapy (PDT) has been the focus of research and development to facilitate medical field application. However, PDT is still much less known than conventional treatments (e.g. chemotherapy, radiotherapy, surgery). Despite advantages of PDT for a variety of applications, it has not achieved an equally prominent position in clinical practice. A critical aspect during PDT treatments is the PDT efficacy and the determination of accurate treatment protocols. Three main strategies are highlighted in this thesis, to elucidate mechanisms at the molecular level to enhance the PDT efficiency and furthermore facilitate more accurate and reliable PDT protocols: (i) optimization of the photosensitizer (PS) interaction with membranes, (ii) specificity of PS to intracellular targets and (iii) bioavailability of photosensitizers in a monomeric form by using a nanocarrier. A series of amphiphilic photosensitizers (PpNetNI, CisDiMPyP, TPPS2a, AlPcS2a) were evaluated in terms of photophysical and photochemical properties, membrane interaction and membrane photodamage. Data indicated that the different peripheral groups do not significantly affect the photophysical properties of the porphyrins. However, these groups directly impact the membrane interaction. CisDiMPyP exhibits a higher binding to membranes than PpNetNI (both are positively-charged amphiphilic porphyrins with similar photophysical properties), probably because the phenyl peripheral hydrophobic groups provide a steric barrier, avoiding π-π stacking and also increasing the hydrophobic interaction with the membrane. Although TPPS2a contains two negatively charged groups, it has a larger interaction with negatively charged membranes than PpNetNI indicating that both, hydrophobic and dipolar, interactions play an important role for the affinity of these molecules to membranes. The smaller incorporation of AlPcS2a into membranes was attributed to the higher rigidity of this molecule and larger polarity in the center of chromophore due to the metal. Within the series of four amphiphilic photosensitizers studied in membranes, it was selected two porphyrins (CisDiMPyP and TPPS2a) with the best membrane interaction and membrane photodamage to further investigations in eukaryotic cells. While the structure and the photophysical properties ofCisDiMPyP and TPPS2a are similar, these PS have opposite charges. As a consequence of the opposite charges, each photosensitizer aims at different organelle. In case of the positively-charged porphyrin (CisDiMPyP), it localizes mainly in mitochondria and triggersapoptotic death. On the other hand, the negatively-charged porphyrin (TPPS2a) are directed to lysosomes, impairing the autophagy pro-survival functions and resulting in autophagy-associated cell death. The lysosomal photodamage and induction of autophagy-associated cell death caused by TPPS2a showed to be more effective to inhibit cell proliferation, even though the cellular uptake and the membrane binding efficiency of TPPS2a is lower. This goes against some paradigms in literature which describe a relationship between stronger phototoxicity and larger interaction with membranes and defend mitochondria as key intracellular target. Tyrosine-derived nanospheres were used as nanocarriers for porphyrins (CisDiMPyP and TPPS2a) aiming at an increased bioavailability of the PS. The choice of this copolymers is due its biodegrability, biocompatibility, high loading capacity, high micellization yield and extremely stable micelles. Although porphyrins provide no changes to nanospheres properties (e.g. size, superficial charge, stability), Tyrospheres are able to improve photophysical and photochemical properties with better 1O2 generation and lifetimes. Moreover, Tyrospheres enhance phototoxicity of porphyrins without alter subcellular localization and cell death mechanism.